2023
DOI: 10.1002/cnma.202300124
|View full text |Cite
|
Sign up to set email alerts
|

Metallo‐Supramolecular Structures Binding CO2: Self‐Assembly of Fluorescent Nanoparticles Based on Pyridine Derivatives of Pillar[5]arene and Cu(I)

Abstract: Decasubstituted pillar[5]arenes containing 2-and 4thiopyridine and thiophenol fragments were synthesized for the first time. The spatial structure of pillar[5]arene containing 4-thiopyridine fragments was established by X-ray crystallography. Unique fluorescent self-assembling metallosupramolecular structures with Cu(I) cations were synthesized based on the macrocycle. It was found that the obtained metallo-supramolecular structures are able to bind CO 2 , which was confirmed by a number of methods. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In methanol, denser and stable nanoassociates 3 are formed at a lower concentration, which is due to the higher polarity of methanol (ε = 32.63 [19]) compared to trichloromethane (ε = 4.64 [19]) with more pronounced hydrophobic effect of the solvent, leading to the formation of macrocycle nanoparticles [20]. It is known from the literature data [21,22] that pillar [5]arenes do not form associates in DMSO due to strong solvation of macrocycles. In this regard, the self-association of bis-pillar [5]arene 3 in aprotic DMSO (ε = 45 [19]) was additionally studied, and it was shown that no stable self-associates of macrocycle 3 are formed in the entire studied concentration range.…”
Section: Resultsmentioning
confidence: 99%
“…In methanol, denser and stable nanoassociates 3 are formed at a lower concentration, which is due to the higher polarity of methanol (ε = 32.63 [19]) compared to trichloromethane (ε = 4.64 [19]) with more pronounced hydrophobic effect of the solvent, leading to the formation of macrocycle nanoparticles [20]. It is known from the literature data [21,22] that pillar [5]arenes do not form associates in DMSO due to strong solvation of macrocycles. In this regard, the self-association of bis-pillar [5]arene 3 in aprotic DMSO (ε = 45 [19]) was additionally studied, and it was shown that no stable self-associates of macrocycle 3 are formed in the entire studied concentration range.…”
Section: Resultsmentioning
confidence: 99%